Estudo da redução de acetofenonas utilizando biocatalizadores da região amazônica para obtenção de substâncias com elevada pureza enantiomérica de interesse farmacológico - Santiago, Paulo Alexandre Lima (2017)
The search for new biocatalysts is of great interest to the biotechnology and pharmaceutical industries. Enzymes are substances found in plants and in microorganisms, and present themselves as excellent catalysts due to their ability to synthesize chemical substances that are biologically active. Some of these compounds are widespread in drug production, such as enantiomerically pure alcohols. Its synthesis can be carried out using whole cells of vegetables or microorganisms in the asymmetric bioreduction reactions of ketones. Considering the vast biodiversity present in the Amazon region and the need for research in this area, this work aimed to bioprospect new biocatalysts, in order to evaluate its potential on the enantioselective bioreduction reactions of acetophenones. The vegetables Daucus carota (carrot), Zingiber officinale (ginger), Manihot esculenta (cassava), Ipomoea potatoes (sweet potato), Solanum melongena (eggplant), and different parts of Amazon plants Cissus gongylodes (Cipó kupá), Solanum sessiliflorum (cubiu) and Xanthosoma violaceum were tested. Different fungi strains of the genus Aspergillus were also tested. The fungi were evaluated regarding its production of alcohol dehydrogenase (ADH), enzyme envolved in the bioreduction reactions. The reactios of p-aminoacetophenone, p-hydroxyacetophenone, p-nitroacetophenone and p-methoxy-mnitroacetophenone were evaluated in three reaction systems: organic (hexane), biphasic (hexane and buffer), and aqueous (buffer). The fungi were cultivated for a period of five days, then were filtered and set to dry. For the vegetables, an assepsia step was performed and then they were cut into small pieces. Thereafter, 50 mg of the dried mycelia or 10 g of the sliced vegetables were added to the reaction medium (40 mL) containing the previously solubilized carbonyl substrates. After 24 hours, the reaction was analyzed by gas chromatography equipped with a chiral column. All tested fungi produced ADH, and 5 strains were selected for the biocatalytic reactions. Fungus A. brasiliensis presented the best convertion percentages for the reduction of p-nitroacetophenone (c = 53.7%), and p-methoxy-m-nitroacetophenone (c = 32.2%), both in a biphasic system. In organic medium, the strain was able to reduce the paminoacetophenone (c = 11%). All these reactions presented enantiomeric excess > 99%. Among the tested vegetables, the reduction of p-aminoacetophenone mediated by the tuber of purple taioba presented an outstanding result (c = 93.6%) of only one chiral alcohol, in organic medium. For the reduction of p-hydroxyacetophenone, the carrot was the best biocatalyst, forming only one enantiomer, with 45.5% conversion in biphasic medium. For pnitroacetophenone, the cipó-kupá promoted the formation of only one product with 13.9% conversion in the two-phase medium. For p-methoxy-m-nitroacetophenone, cassava and purple taioba tuber provided 34.6% conversion to the chiral alcohol in aqueous medium. To evaluate the influence of reaction time, substrate concentration and pH over the conversion values, it was performed an experimental design for some of the biocatalytic systems. For A. brasiliensis, time and pH were the variables that significantly influenced chiral alcohol production (p > 0.5), with the shortest time and the highest pH leading to the highest conversion rates. For the tests performed with the vegetables, sweet potato was directly influenced by pH during the reduction reaction of p-nitroacetophenone (p > 00.5). In this work were obtained results that demonstrate the biocatalytic potential of fungi of the genus Aspergillus and of several plants found in the Amazon region, especially purple taioba. It is expected that researchs on this area can be carried out to explore the biotechnological potential of these organisms with an emphasis on biocatalysis. Key words: Biocatalysis, Aspergillus, Vegetables, Biorreduction, Enantioselectivity.